Ornamen Masjid Jami Kajen serta Kontribusinya dalam Penguatan Pendidikan Karakter di Madrasah Ibtidaiyah - M. Sofyan Alnashr (Jurusan PGMI FTIK IAIN Metro Lampung, 2020)
This study aims to explain the meaning of ornaments contained in the Jami Kajen Mosque and its contribution in strengthening character education of children in Madrasah Ibtidaiyah. This research is a qualitative descriptive study with a philosophical interpretative approach to find the meaning behind the mosque's ornaments then relate it to teaching material of PAI MI and find its contribution to the strengthening of the character education of MI students. The results showed, first, the ornaments contained in the Jami Kajen Mosque contained philosophical meaning in containing Islamic teachings and local wisdom conveyed by Shaykh Mutamakkin through art. Ornaments with symbolic meanings are found in the Jami Kajen Mosque, namely the sculpture of Kuntul Nucuk Bulan, Naga Aji Saka, Gajah-Trisula-Taman, Corresponding Board, and Mosque Sky Calligraphy. The teachings conveyed came from Islamic teachings sourced from the Qur'an and Hadith as well as teachings from Javanese tradition and culture. Second, ornaments with the meaning of the content of Islamic teachings and local culture in the Jami Kajen Mosque make a major contribution to the strengthening of the character of MI students through learning based on local wisdom of the Jami Kajen Mosque as a source of learning and learning media. Active learning and contextual learning to strengthen the character of MI students can be done by making the ornaments of the Jami Kajen Mosque as the basis of learning of PAI MI.